DNA methylomes undergo distinct waves of remodeling during thymic T cell development and do not acquire a proliferation-induced imprint - Frederik Hamm; Emilie Coppin; Mingxing Yang; Alisier Malard; Anne Schulze; Marcel Finke; Dania Hamo; Abdulrahman Salhab; Gilles Gasparoni; Jörn Walter; Mir-Farzin Mashreghi; Joachim Photiadis; et al. (Cell Reports)
Summary: Dynamic changes of the DNA methylation (DNAmeth) landscape drive differentiation of mature T lymphocytes. However, the role of DNAmeth-mediated regulation in thymocyte development remains unclear. Thus, we generated genome-wide DNAmeth profiles of eight defined human thymocyte subsets, revealing two waves of DNAmeth remodeling: first before TCR rearrangement, then during final maturation. Transcriptomic changes occurred also during phases of DNAmeth stability, indicating decoupled dynamics of epigenetic and transcriptional regulation. In contrast to mature T cells, thymocytes were protected from proliferation-induced changes in the DNA methylome. Finally, the DNAmeth profiles were useful as biomarkers to assess the quality of an in vivo mouse model of human T cell development. This study revealed unexpected dynamics of DNAmeth-mediated control of human thymocyte development and displayed the capacity of DNAmeth profiles to serve as biomarkers for successful T cell generation in model systems and, as a possible future application, during manufacturing of therapeutic cell products.